The Development of Public Health Policies for the LGBTQIA+ Public in Brazil (Research, Society and Development, 2022)
Introduction: Various particularities and guarantees arising from the issue of LGBT rights are observed. Several public health policies have been implemented by the federal government to address the specific issues of this population. However, the disparity in treatment suffered by these individuals in the public network, added to the high rates of violence and discrimination suffered by the population, ends up remaining constant and thus creates a challenge for public institutions. The objective of the study is to carry out a critical analysis of the effectiveness of public policies for the LGBTQIA+ population in recent decades. Methodology: This is an integrative literature review carried out through the Scielo and BVS databases containing publications between 2009 and 2022. Results: For the composition of the sample, 7 scientific articles were selected following the inclusion and exclusion criteria, in addition to theoretical books and materials from the Ministry of Health obtained throughout the research. Conclusion: Despite the progress of services in meeting the demands of the LGBTQIA+ population, in practice, there are still gaps in the implementation of policies to meet them. Therefore, public health policies should be more precise and effective to reach all citizens and, consequently, promote an improvement in the health condition and vulnerability of the LGBT community.